Kecemasan dan Kepribadian Neoritik-Teori Karen Horney - Risya Fadhilla; Luthfia Zahra; Mutia Nurhaliza; Maya Chofifah (Lembaga Yasin AlSys, 2023)
Horney believed that personality develops as a result of a complex interaction of biological, environmental, and social factors. He argues that individuals who experience bullying can experience significant internal conflicts that affect personality development. One of his forms of optimism is his belief in biological powers that will not punish us in the form of conflict, anxiety, neurosis or something universal in personality. According to Horney, each person is unique. If neurotic behavior occurs, then it occurs because of social encouragement in childhood. The parent-child relationship may be satisfying, but it may also be frustrating for the child's need for fulfillment. If their needs are not met, the result is neurotic behavior, neurosis or conflict can be avoided if the child grows up full of love, acceptance and trust. The results of the study showed that there was a psychological impact on the students of MA Al-ittihadiyah Medan as victims of bullying as a result of the bullying incidents they experienced at school, such as feeling afraid, anxious, worried at school and having difficulty concentrating in class, and feeling stressed.